Intumescent ethylene-vinyl acetate copolymer: Reaction to fire and mechanistic aspects. (March 2019) - Bourbigot, Serge; Sarazin, Johan; Samyn, Fabienne; Jimenez, Maude
Abstract: The concept of intumescence was applied to flame retard ethylene vinyl acetate copolymer (EVA). The paper examines two types of intumescence based on expandable graphite (EG, physical expansion) and on modified ammonium polyphosphate (AP760, chemical expansion). The incorporation of expandable graphite (EG) at relatively low loading (10 wt%) in EVA permits the reduction up to 65% of peak of heat release rate (pHRR) measured by cone calorimetry. The mode of action occurs via the formation of an expanded carbonaceous layer acting mainly as heat barrier limiting heat and mass transfer as evidenced by the temperature measurement as a function of time during cone calorimetry. The incorporation of small amount of ZnCO3 in EVA-AP760 enhances strongly the performance: pHRR was not reduced using the sole AP760 while it is decreased by 54% when only 2 wt% of AP760 is substituted by ZnCO3 . A strong synergistic effect was therefore observed. Solid state NMR of 31 P and 13 C on cone residues prepared at different characteristic times evidenced the mechanism involved is the reinforcement of the protective char by the formation of phosphate glass limiting the creation of cracks and increasing the char strength. Graphical abstract: Image 1 Highlights: Two types of intumescence: physical and chemical expansion. Low loading of expandable graphite provides lower pHRR (lower than that of EVA/ATH at 65 wt%). Zinc carbonate is a superior synergist for conventional intumescent EVA (chemical expansion). Zinc carbonate: reinforcement of the protective char by the formation of phosphate glass.